Hiring people for their abilities and not their disabilities. A qualitative study aimed at identifying the barriers faced by organisations in Gauteng when employing people with disabilities in the business and financial sectors of the economy - Marx, Andrew E. (University of Pretoria, 2013)
Dissertation (MCom (Business Management))--University of Pretoria, 2006.